Investigating the Impact of Problem-Based Learning on Students’ Critical Thinking and Learning Autonomy in the Context of Primary Education - Irwan, Alken; Ulumiyah, Dzuhrotul; Dinda, Dinda; Saila, Nurul; Andrayni, Maymunah (Journal of Innovation and Research in Primary Education, 2026)
This study investigates the impact of the Problem-Based Learning (PBL) model on students’ critical thinking skills and learning autonomy in primary education, addressing the limited empirical evidence examining the simultaneous development of these competencies at the elementary school level in Indonesia. The research was conducted in a public elementary school in Bram Itam District involving two sixth-grade classes, Class VI A and Class VI B, each comprising 21 students. A quasi-experimental design with a pretest–posttest control group was employed, using a critical thinking test and a learning autonomy questionnaire as data collection instruments. The results indicated a substantial improvement in the experimental group compared to the control group, with mean critical thinking scores increasing from 68.10 to 84.29 and learning autonomy from 70.43 to 86.05. Independent samples t-test analysis revealed significant differences between groups for both critical thinking (t = 3.42, p < 0.05) and learning autonomy (t = 3.76, p < 0.05). These findings demonstrate that PBL effectively enhances analytical reasoning and self-regulated learning among elementary students. The study supports the integration of PBL as a strategic instructional model to promote higher-order thinking and independent learning in alignment with 21st-century educational demands and the Kurikulum Merdeka reform.